Artificial surfactant and natural surfactant. Comparative study of the effects on premature rabbit lungs. Issue 10 (October 1980) - Morley, C; Robertson, B; Lachmann, B; Nilsson, R; Bangham, A; Grossmann, G; Miller, N
Abstract : Premature newborn rabbits, delivered on day 27 of gestation, were treated with tracheal deposition of dry artificial surfactant containing dipalmitoyl phosphatidylcholine and unsaturated phosphatidylglycerol (7:3), or crude natural surfactant prepared by centrifugation of lung wash from adult rabbits. Before receiving surfactant, the animals were allowed to breathe for 7–27 min; they were then subjected to artificial ventilation under standardised conditions. In comparison with littermate controls, both groups of surfactant-treated animals showed statistically significant improvement in lung-compliance 30 and 60 min after onset of ventilation. However, necrosis of bronchiolar epithelium and hyaline membranes was present in nearly all animals, even in those treated with natural surfactant; this suggests that in order to prevent epithelial lesions, surfactant should be given as soon as possible and preferably at birth. Our findings confirm earlier observations that treatment with supplementary surfactant has a beneficial effect on lung mechanics in the premature neonate. The fact that this effect can be obtained not only with natural surfactant but also with dry artificial surfactant should increase the possibility of clinical application.